2015
DOI: 10.3109/21691401.2015.1008510
|View full text |Cite
|
Sign up to set email alerts
|

Comparison, synthesis and evaluation of anticancer drug-loaded polymeric nanoparticles on breast cancer cell lines

Abstract: Breast cancer is a major form of cancer, with a high mortality rate in women. It is crucial to achieve more efficient and safe anticancer drugs. Recent developments in medical nanotechnology have resulted in novel advances in cancer drug delivery. Cisplatin, doxorubicin, and 5-fluorouracil are three important anti-cancer drugs which have poor water-solubility. In this study, we used cisplatin, doxorubicin, and 5-fluorouracil-loaded polycaprolactone-polyethylene glycol (PCL-PEG) nanoparticles to improve the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…Several reports in recent years showed that chrysin is a candidate for cancer therapy in different kinds of cancer cell lines due to it is activity to inhibit the cell proliferation and induction of cell death via apoptosis pathway [11,12]. Although, chrysin possesses anticancer properties, its poor water solubility limited its biocompatibility, bioavailability and biomedical applications, indicating an important problem for cancer treatment [13] because of quick metabolism, low absorption and rapid systemic elimination [2]. One of the approaches to overcome this problem is the use of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports in recent years showed that chrysin is a candidate for cancer therapy in different kinds of cancer cell lines due to it is activity to inhibit the cell proliferation and induction of cell death via apoptosis pathway [11,12]. Although, chrysin possesses anticancer properties, its poor water solubility limited its biocompatibility, bioavailability and biomedical applications, indicating an important problem for cancer treatment [13] because of quick metabolism, low absorption and rapid systemic elimination [2]. One of the approaches to overcome this problem is the use of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…To resolve this problem, nanotechnology has offered water soluble and biocompatible NPs, which their physicochemical properties make them good choices to deliver various types of the anti-cancer drugs [22]. Dissolving drugs-loaded NPs in water results in the hydrophilic shell and hydrophobic core for stabilization of NP and loaded drug, respectively [23]. On the other hand, encapsulating drugs in engineered NPs can improve the safety of drug delivery and enable directed drug delivery to target tissues without damages to the healthy ones [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Artemisia aucheri-loaded magnetic hydrogel nanocomposite was fabricated through hydrogel dispersion in NaOH in the presence of magnetic nanoparticles (MNPs) and Artemisia aucheri extract [18]. Fifty (50 mg) of extract and 100 mg of MNPs were dispersed in 40 ml of 25 mM NaOH solution, the solution is sonicated at 0.5 cycle, 50 % amplitude for 15 min.…”
Section: Preparation Of Extract-loaded Magnetic Hydrogel Nanocompositementioning
confidence: 99%